2019
DOI: 10.21873/anticanres.13385
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Enoxaparin for Prophylaxis of Postoperative Venous Thromboembolism After Esophagectomy: A Single-center Prospective Randomized Controlled Phase II Study

Abstract: Background/Aim: This study aimed to assess whether low-molecular-weight heparin (LMWH) is effective and safe in preventing postoperative venous thromboembolism (VTE) in patients undergoing esophageal cancer surgery. Patients and Methods: In this single-institution, prospective, randomized trial, 73 patients with esophageal cancer undergoing esophagectomy were randomly divided into the enoxaparin group (E group) and intermittent pneumatic compression group (I group). The primary endpoint was efficacy of enoxapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
0
13
0
1
Order By: Relevance
“…However, D-dimer has low specificity for VTE and is generally elevated after surgery. Tanaka et al reported that D-dimer increases to about 20 μg/mL after gastric cancer surgery [13] . Therefore, D-dimer is not useful for confirming PE, and it should be measured only when PE is clinically suspected.…”
Section: Discussionmentioning
confidence: 99%
“…However, D-dimer has low specificity for VTE and is generally elevated after surgery. Tanaka et al reported that D-dimer increases to about 20 μg/mL after gastric cancer surgery [13] . Therefore, D-dimer is not useful for confirming PE, and it should be measured only when PE is clinically suspected.…”
Section: Discussionmentioning
confidence: 99%
“…26,28,29,31,38,43 Prophylaxis with LMWH was performed in the studies of Daddi, Attaran, Song, Mantziari, Christensen, Song, Pannucci, and Esme. 30,33,35,36,40,41,42,44 Dentali, Agzarian, and Alai 37,47 compared prophylaxis of LMWH or heparin in patients receiving lung surgery; Tanaka 46 compared prophylaxis of an IPC or enoxaparin in patients who underwent esophagectomy for esophageal cancer;…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka 46 conducted a randomized trial including surgical esophageal cancer patients that were randomly assigned to either prophylaxis of IPC applied from the start of operation to the first ambulation from bed or combination subcutaneous injection of enoxaparin (06:00 PM on the first operation day then twice daily on PODs 2-14) on the first operation day and the same IPC procedure.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Five small Japanese randomised controlled trials assessed mechanical methods of thromboprophylaxis in surgical patients with cancer, with inconsistent findings. 44 , 45 , 46 , 47 , 48 In a network meta-analysis of patients with gynaecological cancer undergoing major abdominopelvic surgery, comparing different methods of thromboprophylaxis, intermittent pneumatic compression plus LMWH was best for VTE prevention. 42 …”
Section: Vte Prophylaxis In Patients With Cancermentioning
confidence: 99%